QUEST Simulation Analysis for Facility Layout Redesign of Handwork Area - Isa, Halim (2010)
The design of manufacturing system is a complex and expensive task especially to small-medium industries. Many problems related to design and operations of manufacturing system are too complex, and as a result the recognition of the applicability of simulation in manufacturing environment is increased. This paper presents an application of simulation modelling within a facility layout of a Handwork Area; Miyazu (M) Sdn Bhd, located in Shah Alam, Selangor. The aim of this study is to analyse and optimise the production flow efficiency at Handwork Area using QUEST® simulation analysis. Consequently, the poor layout designs resulted in inefficiencies in term of heavy congestion at the load and unload stations. The department is struggling to locate the incoming parts from the depot since the pickup and drop off buffet is not properly placed, which results to untidy appearance. To address this problem, simulation modelling was employed. Quest simulation analysis is found to be very powerful tool that can be used in the design phase. Simulation modeling activity is used in this study since it allows verification of the floor design without having to rearrange the actual physical layout. The outcomes of the simulation model can be used as benchmarks for evaluating the efficiency of the new layout.